Isothermal and thermomechanical fatigue behaviour of type 316LN austenitic stainless steel base metal and weld joint - Kumar T.S.; Yadav S.D.; Nagesha A.; Kannan R.; Reddy G.V.P. (My University, 2025)
Thermomechanical fatigue (TMF) studies were carried out on type 316 LN austenitic stainless steel (SS) base metal (BM) and its weld joint (WJ) with a temperature interval of 623–873 K under in-phase (IP) and out-of-phase (OP) combinations of mechanical strain and temperature. Tests were performed under mechanical strain control mode using the strain amplitudes in the range, ±0.25% to ±0.6%. Besides, isothermal low cycle fatigue (IF) tests were also conducted on the weld joint at 873 K. TMF cycling resulted in a slightly higher cyclic stress response (CSR) compared to IF loading for the weld joint. The IP TMF cycling yielded a higher plastic strain amplitude in comparison to OP TMF for both the base metal and the weld joint. Cyclic life of the weld joint is found to be inferior to that of the base metal. The fatigue lives exhibited by the base metal and the weld joint varied in the following sequence: IP TMF < IF < OP TMF. Preferential crack initiation in the weld region owing to embrittlement of transformed δ-ferrite was noticed with an increase in the mechanical strain amplitude under both TMF and IF cycling conditions. Crack initiation and propagation generally occurred in transgranular mode under IF and OP TMF and mixed (trans-plus intergranular) mode under IP TMF cycling. Electron back scattered diffraction (EBSD) measurements were employed to investigate the substructural development in terms of local misorientation distribution, inverse pole figure (IPF) maps and boundary dislocation density (ρ) in the weld metal region, under IF and IP TMF cycling. The dislocation density was found to decrease for both IF and IP TMF cycling compared to the as-welded condition, with the decrease being higher for IF cycling. The TMF data generated for the type 316LN SS base metal and weld joint at different strain ranges in the present study clearly demonstrated a lack of conservatism associated with the current design practice which is based on the IF data at the maximum temperature (Tmax) of the service cycle. © 2019 Elsevier B.V.